Trabalhar em penitenciárias: violência referida pelos trabalhadores e (in)satisfação no trabalho - Alves, Valdir; Binder, Maria Cecília Pereira [UNESP] (Fundação Jorge Duprat Figueiredo de Segurança e Medicina do Trabalho - FUNDACENTRO, 2014)
Objective: to describe work-related characteristics, hear opinions, report aggressions and estimate the degree of work satisfaction among workers of two state prisons in Avaré, São Paulo, Brazil. Methods: cross section epidemiological study, gathering information through anonymous self administered questionnaire. We sought association between work characteristics, opinions and work place aggressions. Results: 301 subjects were enrolled, mostly men (85.4%) whose ages ranged between 30 and 49 years (61.1%) with a mean job time of 12.9 years. 46.8% worked extra hours, 68.2% reported worksite verbal or physical aggression, and threatening. Being engaged in repressive activities and being in straight contact with prisoners show a significant association with suffering aggressions (x2 = 4.31; p = 0.0038 e x2 = 6.65; p = 0.0099, respectively). Only 27.1% of the interviewed prison workers mentioned the desire of keeping their jobs under the same working conditions. There was an association between job dissatisfaction and aggression (x2 = 5.976: p=0.014). Conclusion: this study revealed daily violence that characterizes work in the studied prisons.

Objetivo: descrever aspectos do trabalho, auscultar opiniões, relatar agressões e estimar o grau de satisfação com o trabalho de funcionários de duas penitenciárias estaduais de Avaré - SP. Métodos: estudo epidemiológico transversal, com coleta de informações realizada por meio de questionário auto-aplicável não identificado. Pesquisou-se associação entre aspectos do trabalho, opiniões e histórico de agressões no trabalho. Resultados: participaram 301 sujeitos, majoritariamente homens (85,4%) no grupo etário de 30 a 49 anos (61,1%); tempo médio no serviço 12,9 anos; 46,8% realizavam horas-extras; 68,2% relataram sofrer agressões físicas, verbais ou ameaças no trabalho. Exercer atividade repressiva e contato direto com detentos mostraram associação significativa com sofrer agressões (x2 = 4,31; p = 0,0038 e x2 = 6,65; p = 0,0099, respectivamente). Apenas 27,1% dos entrevistados referiu acreditar na possibilidade de continuar no emprego mantidas as condições de trabalho. Observou-se associação entre insatisfação no trabalho e histórico de agressão (x2 = 5,976: p=0,014). Conclusão: o estudo revela o cotidiano de violência que caracteriza o trabalho nas penitenciárias estudadas.
Penitentiary work; violence referred by workers and (dis)sactisfaction at work
Keywords: Trabalho penitenciário; satisfação no trabalho; saúde do trabalhador; Penitentiary work; work satisfaction; worker' health